Self-adjuvant nano-drug loaded with copper peroxide as well as preparation method and application of self-adjuvant nano-drug
Through the self-adjuvanted nanodrug loaded with copper peroxide, the self-generated nano-aluminum adjuvant and self-supply H2O2 ability in the tumor microenvironment is used to solve the problem of poor tumor treatment effect in the prior art, and the effect of significantly improving the tumor treatment effect is achieved.
Patent Information
- Application Number
- CN202510050350.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-04-25
AI Technical Summary
Nanomaterials with enzyme-like activity in the prior art are poor in tumor treatment, mainly due to the limited content of endogenous H2O2 in tumor cells and the severely limited therapeutic effect.
A self-adjuvanted nanodrug loaded with copper peroxide is used. The nanodrug has a core-shell structure, the core is nano aluminum nitride, and the outer shell is hyaluronic acid embedded with copper peroxide quantum dots. This nanodrug can generate nano-aluminum adjuvant in the tumor microenvironment, consume glutathione, self-supply H2O2, and generate a large amount of reactive oxygen species through a Fenton-like reaction, killing cancer cells.
Through autogenerated nano-aluminum adjuvant and self-supply H2O2, the immunosuppressive microenvironment is reversed, the anti-tumor immune response is enhanced, and the tumor treatment effect is significantly improved.
Smart Images

Figure CN119868306A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of nano biomaterials, and in particular relates to a self-adjuvant nano drug loaded with copper peroxide, a preparation method and an application thereof. Background Art
[0002] Cancer is a major health problem for people. In recent years, the incidence and mortality of cancer have been increasing. Therefore, it is crucial to explore new strategies for tumor treatment. Although immunotherapy represented by immune checkpoint inhibitors is considered to be the best candidate strategy for curing tumors, its therapeutic effect is not satisfactory, mainly because malignant tumors have the characteristics of low immunogenicity, immunosuppression and immune escape. Recently, the research on nanodrug preparations has gradually deepened. It not only has the advantages of good biocompatibility, low cost and easy scalable preparation, but also shows great potential in enhancing the effect of immunotherapy, which is expected to revolutionize the prospects of tumor treatment.
[0003] Chemodynamic therapy (CDT) based on nanomaterials with enzyme-like activity can kill tumor cells in a unique way and has received widespread attention in tumor treatment. CDT can achieve tumor treatment by converting H2O2 in tumor cells into ·OH with high cytotoxicity through (quasi-) Fenton catalysis. The large amount of reactive oxygen produced by CDT can increase the level of tumor oxidative stress, which can not only induce immunogenic death, but also reverse the tumor immunosuppressive microenvironment, thereby enhancing the anti-tumor immune response. Therefore, CDT combined with immunotherapy can theoretically significantly improve the effect of tumor treatment. However, the limited endogenous H2O2 content and overexpression of reduced glutathione in tumor cells greatly limit the therapeutic effect of CDT. At the same time, the immunosuppressive microenvironment severely limits the antigen presentation of dendritic cells, making the effect of immunogenic death effect triggering anti-tumor immune response unsatisfactory. Summary of the invention
[0004] In order to overcome the problem of poor tumor treatment effect of nanomaterials with enzyme-like activity in the prior art, the purpose of the present invention is to provide a self-adjuvanted nanomedicine loaded with copper peroxide, a preparation method and an application thereof. The self-adjuvanted nanomedicine has a core-shell structure, that is, the core is nano-aluminum nitride and the shell is hyaluronic acid embedded with copper peroxide quantum dots; the nanomedicine has active / passive targeting functions for tumors, has acidic / glutathione dual stimulation responsive dissociation / decomposition behavior, can self-generate nano-aluminum adjuvant, neutralize slightly acidic tumor microenvironment, consume glutathione, self-supply H2O2, kill cancer cells in the form of immune anti-cancer, and the like.
[0005] To achieve the above purpose, the technical solution adopted by the present invention is as follows: A method for preparing a self-adjuvanted nano drug loaded with copper peroxide comprises the following steps: preparing hydrazide hyaluronic acid; The hydrazide hyaluronic acid is modified on the surface of the nano-aluminum nitride through coordination and electrostatic adsorption to obtain the hyaluronic acid nano-aluminum nitride; Hyaluronan-coated nanoaluminum nitride was used to prepare copper peroxide-loaded self-adjuvanted nanodrugs in situ via copper-hydrazide coordination / mineralization reaction.
[0006] Furthermore, the specific synthesis steps of hydrazide hyaluronic acid are as follows: add 3,3'-dithiodipropionyl hydrazide and N-hydroxysuccinimide to the hyaluronic acid aqueous solution, adjust the pH to 5 to 5.5, then add 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, stir at 30 to 35°C for 12 to 48 hours, dialyze the reaction system against water for 8 to 48 hours, and obtain hydrazide hyaluronic acid after freeze-drying.
[0007] Furthermore, the concentration of the hyaluronic acid aqueous solution is 10 to 20 mg / mL, the mass ratio of hyaluronic acid: N-hydroxysuccinimide: 3,3'-dithiodipropionyl hydrazide: 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride is 10:1:12:1.5 to 10:3:36:4.5, the molecular weight of hyaluronic acid is 8 to 10 kDa, and the degree of hydrazide of the hydrazide hyaluronic acid is 20% to 60%.
[0008] Furthermore, the specific synthesis steps of hyaluronate-treated nano-aluminum nitride are as follows: uniformly mixing a suspension of aluminum nitride in dimethyl sulfoxide with a mixed solution of hydrazide-treated hyaluronic acid in dimethyl sulfoxide and water to obtain hyaluronate-treated aluminum nitride nanoparticles.
[0009] Further, the mass ratio of hydrazide hyaluronic acid to aluminum nitride is 1 to 5:1; The volume ratio of dimethyl sulfoxide to water in the dimethyl sulfoxide / water mixture is 3:1 to 5:1; Homogenous mixing was achieved by stirring at 800 to 1500 rpm for 1 to 4 h.
[0010] Furthermore, the specific synthesis steps of the self-adjuvanted nanodrug loaded with copper peroxide are: mixing the nanosuspension of hyaluronate aluminum nitride nanoparticles with the copper chloride solution, adding the NaOH aqueous solution and mixing evenly, and then adding the H2O2 aqueous solution and mixing evenly to obtain the self-adjuvanted nanodrug loaded with copper peroxide.
[0011] Furthermore, the concentration of the nanosuspension of hyaluronanized aluminum nitride nanoparticles is 1 to 5 mg / mL, the concentration of the copper chloride solution is 1 to 2 mg / mL, and the mass ratio of hyaluronanized aluminum nitride nanoparticles to copper chloride is 1:1 to 4:1.
[0012] Furthermore, the concentration of the NaOH aqueous solution is 0.5 ~ 2.5 mg / mL, the mass fraction of the H2O2 aqueous solution is 10% ~ 30%, and the volume ratio of the nanosuspension of hyaluronic acid aluminum nitride nanoparticles, the NaOH aqueous solution and the H2O2 aqueous solution is 1 ~ 5mL: 10 ~ 100 μL: 6.25 ~ 100 μL.
[0013] A self-adjuvanted nano drug, the particle size of which is 100-300 nm, has the performance of being able to consume glutathione, self-supply H2O2, self-generate nano aluminum adjuvant and Fenton-like catalytic activity.
[0014] Application of a copper peroxide-loaded self-adjuvanted nano drug in the preparation of a drug for treating malignant melanoma.
[0015] Compared with the prior art, the present invention has the following beneficial effects: The hyaluronic acid nano-aluminum nitride prepared by the present invention is modified on the surface of nano-aluminum nitride by hydrazide hyaluronic acid through coordination and electrostatic adsorption. The hydrazide hyaluronic acid used can not only reduce the hydrolysis of nano-aluminum nitride during drug delivery, but also has the active targeting ability mediated by -CD44 receptor, which lays a solid foundation for improving the efficiency of tumor treatment. The self-adjuvanted nano-drug finally prepared by the present invention is obtained by in-situ generation of copper peroxide by coordination of the hydrazide group of hyaluronic acid on the surface of nano-aluminum nitride with copper ions. The disulfide bonds in hyaluronic acid and the copper ions generated by the decomposition of copper peroxide show good glutathione response characteristics, which will consume intracellular glutathione. At the same time, Cu 2+ Reduced to Cu + It also undergoes a Fenton-like reaction with H2O2 to produce a large amount of reactive oxygen species, which can effectively kill tumor cells. In addition, it has the advantages of easy availability of raw materials and simple preparation methods, making it suitable for large-scale production.
[0016] The self-adjuvanted nano drug prepared by the present invention has a particle size range of 100 to 300 nm and a core-shell structure. This particle size range is conducive to efficient enrichment inside the tumor, and can respond to the weakly acidic tumor microenvironment, so that the nano aluminum nitride in its core is decomposed into Al(OH)3-based aluminum adjuvant and NH3. The former can reverse the immunosuppressive microenvironment, while the latter has outstanding pH regulating ability and cell destructive ability, and enhances immune stimulation ability. It combines with CuO2 to present a synergistic anti-tumor effect, and has the advantages of good biosafety and good stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 is the H NMR spectrum of the hydrazide hyaluronic acid (HHA) prepared in Example 1; Figure 2is a transmission electron microscopy image of the transparent acidified aluminum nitride (AlN@HA) nanoparticles in Example 1; Figure 3 is the XRD pattern of AlN@HA nanoparticles in Example 1; Figure 4 This is a transmission electron microscopy image of the self-adjuvanted nanomedicine (AHC) loaded with copper peroxide in Example 1; Figure 5 is the X-ray photoelectron spectrum of the AHC nanoparticles in Example 1; Figure 6 Element mapping spectrum of AHC nanoparticles in Example 1; Figure 7 is the ability of the AHC nanoparticles in Example 1 to produce ·OH under different pH conditions; Figure 8 This is the glutathione consumption capacity curve of the AHC nanoparticles in Example 1; Fig. 9 The pH change curve during the hydrolysis of nano-AlN and nano-particle AHC in Example 1; Fig.10 Cu is the Cu of AHC nanoparticles under different conditions in Example 1 2+ Cumulative release profile; Fig.11 The morphology of nano-AlN and nano-particle AHC after incubation with B16F10 cells for 1h, 4h, and 12h in Example 1; Fig.12 The change of H2O2 content in B16F10 cells after AHC nanoparticles were treated in Example 1; Fig.13 is the consumption capacity of intracellular glutathione by the AHC nanoparticles in Example 1; Fig.14 This is a picture of intracellular pH fluorescent probe staining after AHC nanoparticles and B16F10 cells were co-cultured in vitro for 24 hours in Example 1; Fig.15 The effect of different concentrations of AHC nanoparticles on B16F10 cell viability in Example 1; Fig.16 is the Zeta potential of the AHC particles obtained with different AlN and CuCl2 feed ratios in Example 5; Fig.17 : This is the particle size distribution diagram of AHC particles obtained with different mass ratios of AlN and CuCl2 in Example 6. DETAILED DESCRIPTION
[0018] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present invention are given in the drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly and comprehensively understood.
[0019] The method for preparing the self-adjuvanted nano drug loaded with copper peroxide of the present invention comprises the following steps: the hydrazide-modified hyaluronic acid in the shell is modified on the surface of the nano aluminum nitride in the inner core by coordination and electrostatic adsorption, the copper peroxide quantum dots generated in situ are embedded in the hyaluronic acid shell, the inner core aluminum nitride can be hydrolyzed to generate nano aluminum adjuvant and ammonia in the tumor microenvironment, and the copper peroxide can be decomposed to generate copper ions and hydrogen peroxide that can undergo a Fenton-like reaction.
[0020] Specifically, the method for preparing the self-adjuvanted nano drug loaded with copper peroxide comprises the following steps: First, a shell hydrazide hyaluronic acid was synthesized, and 3,3'-dithiodipropionyl hydrazide was grafted onto hyaluronic acid using a carbodiimide method to obtain hydrazide hyaluronic acid. The specific steps were as follows: 3,3'-dithiodipropionyl hydrazide and N-hydroxysuccinimide were added to a hyaluronic acid (HA) aqueous solution with a concentration of 10 to 20 mg / mL at room temperature, and then the pH of the solution was adjusted to 5 to 5.5, and then 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride was added (the mass ratio of hyaluronic acid: N-hydroxysuccinimide: 3,3'-dithiodipropionyl hydrazide: 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride was 10:1:12:1.5 to 10:3:36:4.5), and the reaction system was dialyzed against water for 8 to 48 hours after stirring at 30 to 35°C for 12 to 48 hours. h, and freeze-dried to obtain hydrazide hyaluronic acid. The molecular weight of hyaluronic acid used to prepare hydrazide hyaluronic acid is 8 to 10 kDa, and the degree of hydrazide of the obtained hydrazide hyaluronic acid is 20% to 60%; the molecular weight cutoff of the dialysis bag for dialysis is 0.5 to 3 kDa, and the freeze-drying conditions are -20 to 30°C and 24 to 48 h.
[0021] Then, it was modified on the surface of nano-aluminum nitride to prepare hyaluronic acid nano-aluminum nitride. The specific process was as follows: 2 to 10 mg of hydrazide hyaluronic acid was dissolved in 1 to 5 mL of a dimethyl sulfoxide / water mixture with a volume ratio of 3:1 to 5:1 to obtain a hydrazide hyaluronic acid solution; then, 2 mg of aluminum nitride with a particle size of 50 to 100 nm was ultrasonically dispersed in 1 to 5 mL of dimethyl sulfoxide, added dropwise to the hydrazide hyaluronic acid solution, and stirred at 800 to 1500 rpm for 1 to 4 hours to make the hydrazide hyaluronic acid more evenly coated on the surface of the nano-aluminum nitride; then, the product was collected by centrifugation and washed with water 2 to 3 times to obtain hyaluronic acid aluminum nitride nanoparticles with a particle size of about 100 to 200 nm and a Zeta potential of -20 to -30 mV.
[0022] Finally, a self-adjuvanted nanodrug containing copper peroxide quantum dots in the shell is prepared in situ through a copper-hydrazide coordination / mineralization reaction, namely, a self-adjuvanted amino nanodrug loaded with copper peroxide. The specific steps are as follows: hyaluronate aluminum nitride nanoparticles are uniformly dispersed in 1 ~ 5 mL of water to obtain a nanosuspension with a concentration of 1 ~ 5 mg / mL; then, under vigorous stirring, the suspension is slowly dripped into 1 ~ 5 mL of a copper chloride solution with a concentration of 1 ~ 2 mg / mL, wherein the mass ratio of hyaluronate aluminum nitride nanoparticles to copper chloride is 1:1 ~ 4:1; after stirring for 5 ~ 20 min, 100 ~ 1000 μL of a 0.5 ~ 2.5 mg / mL NaOH aqueous solution is slowly dripped, and after 5 ~ 10 min, 6.25 ~ 100 μL of a 10% ~ 30% H2O2 aqueous solution is added, and sodium hydroxide and hydrogen peroxide react with copper chloride to generate copper peroxide; finally, after magnetic stirring at 1000 ~ 1500 rpm for 20 ~ 60 min, the precipitate is collected by centrifugation and washed with water for 2 ~ 3 times, a self-adjuvanted nanomedicine containing copper peroxide quantum dots in the shell was obtained, with a particle size of about 100 to 300 nm and a Zeta potential of about +10 to +30 mV. The in-situ generation of copper peroxide on the surface of aluminum nitride can exert a synergistic anti-tumor effect of aluminum nitride and copper peroxide.
[0023] The self-adjuvanted nanomedicine prepared by the present invention has the characteristics of tumor microenvironment responsive decomposition, can consume glutathione, self-supply H2O2, self-generate nano-aluminum adjuvant, exhibit Fenton-like catalytic activity, neutralize the acidity of tumor microenvironment, kill cancer cells and the like, and can achieve anti-tumor treatment through ammonia toxicity and Fenton-like catalytic activity.
[0024] The following are specific embodiments.
[0025] Example 1: A method for preparing a self-adjuvanted amino nano drug loaded with copper peroxide is as follows: First, hydrazide hyaluronic acid was synthesized, and the specific steps were as follows: 1.2 g of 3,3'-dithiodipropionyl hydrazide and 0.1 g of N-hydroxysuccinimide were added to 100 mL of hyaluronic acid aqueous solution with a concentration of 10 mg / mL at room temperature, and then the pH of the solution was adjusted to 5-5.5 with hydrochloric acid, and then 0.15 g of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride was added. After stirring at 30°C for 36 h, the reaction system was dialyzed against water for 48 h, and hydrazide hyaluronic acid with a hydrazide degree of 20% was obtained after freeze-drying.
[0026] Then, hyaluronate-treated nano-aluminum nitride was prepared. The specific steps were as follows: 2 mg of HHA was dissolved in 1 mL of a dimethyl sulfoxide / water mixture with a volume ratio of 3:1; then, 2 mg of aluminum nitride with a particle size of 55 nm was ultrasonically dispersed in 1 mL of dimethyl sulfoxide, added dropwise to the hydrazide-treated hyaluronic acid solution, and stirred for 1 hour under magnetic stirring at 1400 rpm; then, the product was collected by centrifugation and washed with water 3 times to obtain hyaluronate-treated aluminum nitride nanoparticles.
[0027] Finally, a self-adjuvanted nanodrug containing copper peroxide quantum dots in the shell was prepared in situ by copper-hydrazide coordination / mineralization reaction. The specific steps are as follows: 2 mg of hyaluronate aluminum nitride nanoparticles were uniformly dispersed in 1 mL of water, and then slowly dropped into 1 mL of 1 mg / mL CuCl2 solution under vigorous stirring, wherein the mass ratio of hyaluronate aluminum nitride nanoparticles to copper chloride was 2:1. After stirring for 5 min, 200 μL of 2.5 mg / mL NaOH solution was slowly added, and then 12.5 μL of 30% H2O2 aqueous solution was added after 5 min. Finally, after reacting at 1400 rpm with magnetic stirring for 30 min, the precipitate was collected by centrifugation and washed with water 3 times to obtain a self-adjuvanted nanodrug containing copper peroxide quantum dots in the shell, that is, a self-adjuvanted nanodrug loaded with copper peroxide.
[0028] Figure 1 This is the H NMR spectrum of the hydrazide hyaluronic acid prepared in Example 1. Figure 1 The H NMR spectra of hyaluronic acid (HA) and HHA are shown. Figure 1 It can be seen that compared with HA, HHA 1 Two new chemical shifts were found in the H NMR spectrum, located at 2.85 ppm (a) and 2.53 ppm (b), which can be attributed to the methylene signals in TPH, thus confirming that TPH was successfully grafted onto HA.
[0029] Figure 2Figure 1 is a transmission electron microscope image of the AlN@HA nanoparticles in Example 1. Figure 2 Transmission electron microscopy images show that AlN@HA nanoparticles have good dispersion and the average particle size is 189.70 nm.
[0030] Figure 3 is the XRD pattern of AlN@HA nanoparticles in Example 1. Figure 3 As shown in the figure, there is still a lot of AlN in the AlN@HA nanoparticles modified with HHA.
[0031] Figure 4 is a transmission electron microscopy image of the AHC nanoparticles in Example 1. Figure 4 Transmission electron microscopy images show that the particle size of AHC nanoparticles is about 160.53 nm.
[0032] Figure 5 This is the X-ray photoelectron spectrum of the AHC nanoparticles in Example 1.
[0033] Figure 6 This is the mapping spectrum of AHC nanoparticles in Example 1.
[0034] Figure 7 is the ability of the AHC nanoparticles in Example 1 to produce ·OH under different pH conditions. The Fenton-like catalytic ability of AHC was evaluated using TMB colorimetric method. Figure 7 As shown in the figure, as the pH decreases from 6.5 to 5.0, the TMB solution turns into a distinct blue color and exhibits a strong absorption peak at 650 nm, proving that AHC nanoparticles can mediate the occurrence of Fenton-like reactions in an acidic environment, generate a large amount of ·OH, and do not require the addition of additional H2O2. These results indicate that AHC nanoparticles have excellent H2O2 self-supply capacity and Fenton-like catalytic ability, thereby improving the CDT therapeutic effect in the acidic microenvironment of tumors.
[0035] Figure 8 The GSH depletion capacity of AHC nanoparticles in Example 1 was studied by DTNB method. Figure 8 As shown, with the increase of AHC nanodrug concentration, the absorbance at 412 nm decreased rapidly, indicating that AHC can fully consume GSH in the system.
[0036] Fig. 9 The pH curve of the hydrolysis process of nano-AlN and nano-particle AHC in Example 1 is shown in FIG. Fig. 9As shown in the figure, AlN particles without HHA coating underwent a violent hydrolysis reaction in water, and the pH of the suspension rose to 9.5 after 1 h. However, the hydrolysis rate of AHC particles encapsulated by HHA was much slower, indicating that HHA was successfully coated on the surface of AlN particles and inhibited their hydrolysis.
[0037] Fig.10 Cu is the Cu of AHC nanoparticles under different conditions in Example 1 2+ Cumulative release curve. Fig.10 As shown, under physiological conditions of pH 7.4, the Cu 2+ The release rate was relatively slow, with a cumulative release rate of 53.7% in 24 h. When the pH was 5.5, AHC nanoparticles rapidly released Cu 2+ , and the 6 h cumulative release rates reached 85.4%, indicating that AHC nanoparticles have pH-responsive drug release behavior.
[0038] Fig.11 The graphs are shown in Example 1 after incubation of nano-AlN, nano-particle AHC and B16F10 cells for 1h, 4h and 12h. Since AlN and AHC themselves have no fluorescence, they are fluorescently labeled with FITC, and then the uptake of AlN and AHC by cells at different time points (1h, 4h and 12h) is observed. Fig.11 As shown in the figure, the intracellular fluorescence intensity of AlN and AHC nanoparticles gradually increased with the extension of incubation time, indicating that the cell uptake of particles continued to increase. At the same time point, AHC-treated cells showed higher fluorescence intensity compared with AlN. This is because HHA-modified AHC can enter cancer cells through CD44-mediated endocytosis, thereby improving the efficiency of cell uptake of particles.
[0039] Fig.12 The change in H2O2 content after B16F10 cells were treated with AHC nanoparticles in Example 1. The intracellular H2O2 level was quantitatively evaluated by a H2O2 probe to explore the change in intracellular H2O2 content after the addition of AHC. Fig.12 It can be seen that with the increase of AHC nanodrug concentration, the intracellular H2O2 level gradually decreased. AHC has excellent self-supply of H2O2 ability, but its decomposition to produce H2O2 is blocked by Cu 2+ / Cu + The catalytic conversion to ·OH results in a decrease in the H2O2 level.
[0040] Fig.13 The consumption capacity of AHC nanoparticles on intracellular GSH in Example 1. The effect of AHC concentration on intracellular GSH content was evaluated by GSH detection kit, such as Fig.13 As shown, Fig.14 This is a picture of intracellular pH fluorescent probe staining after 24 hours of in vitro co-culture of AHC nanoparticles and B16F10 cells in Example 1. AHC nanoparticles have excellent GSH scavenging ability and are concentration-dependent. The higher the AHC concentration, the more the GSH content decreases.
[0041] Fig.15 The effect of different concentrations of AHC nanoparticles on the viability of B16F10 cells in Example 1. The CCK-8 test was used to evaluate the cytotoxicity of different drugs on B16F10 cells. Fig.15 As shown, AHC nanoparticles showed obvious concentration-dependence and treatment time-dependence in cytotoxicity to tumor cells. The survival rate of treated cells was only 42.8% at a concentration of 100 µg / mL, indicating a significant tumor cell killing effect.
[0042] Example 2 First, hydrazide hyaluronic acid was synthesized, and the specific steps were as follows: 2.4 g 3,3'-dithiodipropionyl hydrazide and 0.2 g N-hydroxysuccinimide were added to 100 mL of hyaluronic acid aqueous solution with a concentration of 10 mg / mL at room temperature, and then the pH of the solution was adjusted to 5-5.5 with hydrochloric acid, and then 0.3 g 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride was added. After stirring at 30°C for 36 h, the reaction system was dialyzed against water for 48 h, and hydrazide hyaluronic acid with a hydrazide degree of 40% was obtained after freeze-drying.
[0043] Then, hyaluronate-treated nano-aluminum nitride was prepared, and the specific steps were as follows: 2 mg of HHA was dissolved in 1 mL of a dimethyl sulfoxide / water mixture with a volume ratio of 3:1; then, 2 mg of aluminum nitride with a particle size of 50 nm was ultrasonically dispersed in 2 mL of dimethyl sulfoxide, added dropwise to the hydrazide-treated hyaluronic acid solution, and stirred at 800 rpm for 4 hours; then, the product was collected by centrifugation and washed with water 3 times to obtain hyaluronate-treated aluminum nitride nanoparticles.
[0044] Finally, a self-adjuvanted nanodrug containing copper peroxide quantum dots in the shell was prepared in situ by copper-hydrazide coordination / mineralization reaction. The specific steps were as follows: 3 mg of hyaluronate aluminum nitride nanoparticles were uniformly dispersed in 1 mL of water, and then slowly dropped into 1 mL of 1 mg / mL CuCl2 solution under vigorous stirring, wherein the mass ratio of hyaluronate aluminum nitride nanoparticles to copper chloride was 3:1. After stirring for 5 min, 1 mL of 0.5 mg / mL NaOH solution was slowly added, and then 37.5 μL of 30% H2O2 aqueous solution was added after 5 min. Finally, after reacting under magnetic stirring at 1000 rpm for 60 min, the precipitate was collected by centrifugation and washed with water 3 times to obtain a self-adjuvanted nanodrug containing copper peroxide quantum dots in the shell.
[0045] Example 3 First, hydrazide hyaluronic acid was synthesized. The specific steps were as follows: 3.6 g of 3,3'-dithiodipropionyl hydrazide and 0.3 g of N-hydroxysuccinimide were added to 100 mL of hyaluronic acid aqueous solution with a concentration of 10 mg / mL at room temperature, and the pH of the solution was adjusted to 5-5.5 with hydrochloric acid. Then, 0.45 g of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride was added, and the reaction system was dialyzed against water for 48 hours after stirring at 30°C for 36 hours. After freeze-drying, hydrazide hyaluronic acid with a hydrazide degree of 60% was obtained.
[0046] Then, hyaluronate-treated nano-aluminum nitride was prepared. The specific steps were as follows: 5 mg HHA was dissolved in 5 mL of a dimethyl sulfoxide / water mixture with a volume ratio of 4:1; then, 2 mg of aluminum nitride with a particle size of 100 nm was ultrasonically dispersed in 4 mL of dimethyl sulfoxide, added dropwise to the hydrazide-treated hyaluronic acid solution, and stirred at 1500 rpm for 1 hour; then, the product was collected by centrifugation and washed with water 3 times to obtain hyaluronate-treated aluminum nitride nanoparticles.
[0047] Finally, a self-adjuvanted nanodrug containing copper peroxide quantum dots in the shell was prepared in situ by copper-hydrazide coordination / mineralization reaction. The specific steps were as follows: 2 mg of hyaluronate aluminum nitride nanoparticles were uniformly dispersed in 2 mL of water, and then slowly dropped into 1 mL of 2 mg / mL CuCl2 solution under vigorous stirring, wherein the mass ratio of hyaluronate aluminum nitride nanoparticles to copper chloride was 1:1. After stirring for 15 min, 1 mL of 1 mg / mL NaOH solution was slowly added, and then 25 μL of 30% H2O2 aqueous solution was added after 8 min. Finally, after reacting under magnetic stirring at 1500 rpm for 20 min, the precipitate was collected by centrifugation and washed with water 3 times to obtain a self-adjuvanted nanodrug containing copper peroxide quantum dots in the shell.
[0048] Example 4 First, hydrazide hyaluronic acid was synthesized. The specific steps were as follows: 1.2 g 3,3'-dithiodipropionyl hydrazide and 0.1 g N-hydroxysuccinimide were added to 100 mL of hyaluronic acid aqueous solution with a concentration of 10 mg / mL at room temperature, and the pH of the solution was adjusted to 5-5.5 with hydrochloric acid. Then, 1.5 g 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride was added. After stirring at 30°C for 36 h, the reaction system was dialyzed against water for 48 h, and hydrazide hyaluronic acid with a hydrazide degree of 20% was obtained after freeze-drying.
[0049] Then, hyaluronate-treated nano-aluminum nitride was prepared. The specific steps were as follows: 10 mg HHA was dissolved in 3 mL of a dimethyl sulfoxide / water mixture with a volume ratio of 5:1; then, 2 mg of aluminum nitride with a particle size of 70 nm was ultrasonically dispersed in 5 mL of dimethyl sulfoxide, added dropwise to the hydrazide-treated hyaluronic acid solution, and stirred at 1200 rpm for 2 hours; then, the product was collected by centrifugation and washed with water three times to obtain hyaluronate-treated aluminum nitride nanoparticles.
[0050] Finally, self-adjuvanted nanomedicines containing copper peroxide quantum dots in the shell were prepared in situ by copper-hydrazide coordination / mineralization reaction. The specific steps were as follows: 10 mg of hyaluronate aluminum nitride nanoparticles were uniformly dispersed in 5 mL of water, then slowly dropped into 5 mL of 2 mg / mL CuCl2 solution under vigorous stirring, and then 1 mL of 2.5 mg / mL NaOH solution was slowly added after stirring for 20 min, and then 100 μL of 10% H2O2 aqueous solution was added after 10 min; finally, after reacting with magnetic stirring at 1200 rpm for 40 min, the precipitate was collected by centrifugation and washed with water 3 times to obtain self-adjuvanted nanomedicines containing copper peroxide quantum dots in the shell.
[0051] Example 5 First, hydrazide hyaluronic acid was synthesized, and the specific steps were as follows: 1.19 g of 3,3'-dithiodipropionyl hydrazide and 0.1 g of N-hydroxysuccinimide were added to 100 mL of hyaluronic acid aqueous solution with a concentration of 10 mg / mL at room temperature, and the pH of the solution was then adjusted to 5-5.5 with hydrochloric acid, and then 0.144 g of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride was added. After stirring at 30°C for 36 h, the reaction system was dialyzed against water for 48 h, and hydrazide hyaluronic acid with a hydrazide degree of 20% was obtained after freeze-drying.
[0052] Then, hyaluronate-treated nano-aluminum nitride was prepared. The specific steps were as follows: 2 mg of HHA was dissolved in 1 mL of a dimethyl sulfoxide / water mixture with a volume ratio of 3:1; then, 2 mg of aluminum nitride with a particle size of 55 nm was ultrasonically dispersed in 1 mL of dimethyl sulfoxide, added dropwise to the hydrazide-treated hyaluronic acid solution, and stirred for 1 hour under magnetic stirring at 1400 rpm; then, the product was collected by centrifugation and washed with water 3 times to obtain hyaluronate-treated aluminum nitride nanoparticles.
[0053] Finally, a self-adjuvanted nanodrug containing copper peroxide quantum dots in the shell was prepared in situ by copper-hydrazide coordination / mineralization reaction. The specific steps were as follows: 2 mg of hyaluronate aluminum nitride nanoparticles were uniformly dispersed in 1 mL of water, and then slowly dropped into 2 mL of 1 mg / mL CuCl2 solution under vigorous stirring, wherein the mass ratio of hyaluronate aluminum nitride nanoparticles to copper chloride was 1:1. After stirring for 5 min, 200 μL of 2.5 mg / mL NaOH solution was slowly added, and then 25 μL of 30% H2O2 aqueous solution was added after 5 min. Finally, after reacting under magnetic stirring at 1400 rpm for 30 min, the precipitate was collected by centrifugation and washed with water 3 times to obtain a self-adjuvanted nanodrug containing copper peroxide quantum dots in the shell.
[0054] Fig.16 is the Zeta potential of AHC particles obtained with different AlN and CuCl2 feed ratios, such as Figure 6 As shown in the figure, when the mass ratio of AlN:CuCl2 is 1:1, the particles show serious agglomeration, the Zeta potential is only 0.5 mV, and the particles are extremely unstable. 2+ The content is too high, during the reaction, Cu 2+ Coordination with HHA on the adjacent AlN surface results in bridging and adhesion of the particles, leading to large-scale agglomeration.
[0055] Example 6 First, hydrazide hyaluronic acid was synthesized, and the specific steps were as follows: 1.2 g of 3,3'-dithiodipropionyl hydrazide and 0.1 g of N-hydroxysuccinimide were added to 100 mL of hyaluronic acid aqueous solution with a concentration of 10 mg / mL at room temperature, and then the pH of the solution was adjusted to 5-5.5 with hydrochloric acid, and then 0.15 g of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride was added. After stirring at 30°C for 36 h, the reaction system was dialyzed against water for 48 h, and hydrazide hyaluronic acid with a hydrazide degree of 20% was obtained after freeze-drying.
[0056] Then, hyaluronate-treated nano-aluminum nitride was prepared. The specific steps were as follows: 2 mg of HHA was dissolved in 1 mL of a dimethyl sulfoxide / water mixture with a volume ratio of 3:1; then, 2 mg of aluminum nitride with a particle size of 55 nm was ultrasonically dispersed in 1 mL of dimethyl sulfoxide, added dropwise to the hydrazide-treated hyaluronic acid solution, and stirred for 1 hour under magnetic stirring at 1400 rpm; then, the product was collected by centrifugation and washed with water 3 times to obtain hyaluronate-treated aluminum nitride nanoparticles.
[0057] Finally, a self-adjuvanted nanodrug containing copper peroxide quantum dots in its shell was prepared in situ by copper-hydrazide coordination / mineralization reaction. The specific steps were as follows: 2 mg of hyaluronate aluminum nitride nanoparticles were uniformly dispersed in 1 mL of water, and then slowly dropped into 0.5 mL of 1 mg / mL CuCl2 solution under vigorous stirring, wherein the mass ratio of hyaluronate aluminum nitride nanoparticles to copper chloride was 4:1. After stirring for 5 min, 100 μL of 2.5 mg / mL NaOH solution was slowly added, and then 6.25 μL of 30% H2O2 aqueous solution was added after 5 min. Finally, after reacting under magnetic stirring at 1400 rpm for 30 min, the precipitate was collected by centrifugation and washed with water 3 times to obtain a self-adjuvanted nanodrug containing copper peroxide quantum dots in its shell.
[0058] Fig.17 The particle size distribution diagram of AHC particles obtained with different mass ratios of AlN and CuCl2 is shown in Figure 2. Fig.17 As shown in the figure, when the feed ratio of AlN to CuCl2 is 2:1 and 4:1, the average particle size of the obtained AHC particles is 160.53 nm and 180.53 nm, and the potential becomes 23.6 mV and 18.0 mV, respectively. This shows that the nanoparticle size of the drug obtained when the mass ratio of AlN to CuCl2 is 2:1 is smaller and more stable than that when the mass ratio of AlN to CuCl2 is 4:1.
[0059] Example 7 First, hydrazide hyaluronic acid was synthesized, and the specific steps were as follows: 3.6 g of 3,3'-dithiodipropionyl hydrazide and 0.3 g of N-hydroxysuccinimide were added to 100 mL of hyaluronic acid aqueous solution with a concentration of 10 mg / mL at room temperature, and then the pH of the solution was adjusted to 5-5.5 with hydrochloric acid, and then 0.45 g of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride was added. After stirring at 30°C for 36 h, the reaction system was dialyzed against water for 48 h, and hydrazide hyaluronic acid with a hydrazide degree of 60% was obtained after freeze-drying.
[0060] Then, hyaluronate-treated nano-aluminum nitride was prepared. The specific steps were as follows: 2 mg of HHA was dissolved in 1 mL of a dimethyl sulfoxide / water mixture with a volume ratio of 3:1; then, 2 mg of aluminum nitride with a particle size of 55 nm was ultrasonically dispersed in 1 mL of dimethyl sulfoxide, added dropwise to the hydrazide-treated hyaluronic acid solution, and stirred for 1 hour under magnetic stirring at 1400 rpm; then, the product was collected by centrifugation and washed with water 3 times to obtain hyaluronate-treated aluminum nitride nanoparticles.
[0061] Finally, self-adjuvanted nanomedicines containing copper peroxide quantum dots in the shell were prepared in situ by copper-hydrazide coordination / mineralization reaction. The specific steps were as follows: 2 mg of hyaluronate aluminum nitride nanoparticles were uniformly dispersed in 1 mL of water, and then slowly dropped into 1 mL of 1 mg / mL CuCl2 solution under vigorous stirring, wherein the mass ratio of hyaluronate aluminum nitride nanoparticles to copper chloride was 2:1. After stirring for 5 min, 200 μL of 2.5 mg / mL NaOH solution was slowly added, and after 5 min, 12.5 μL of 30% H2O2 aqueous solution was added. Finally, after reacting at 1400 rpm with magnetic stirring for 30 min, the precipitate was collected by centrifugation and washed with water 3 times to obtain self-adjuvanted nanomedicine loaded with copper peroxide.
[0062] Example 8 First, hydrazide hyaluronic acid was synthesized, and the specific steps were as follows: 1.2 g of 3,3'-dithiodipropionyl hydrazide and 0.1 g of N-hydroxysuccinimide were added to 100 mL of hyaluronic acid aqueous solution with a concentration of 10 mg / mL at room temperature, and then the pH of the solution was adjusted to 5-5.5 with hydrochloric acid, and then 0.15 g of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride was added. After stirring at 30°C for 36 h, the reaction system was dialyzed against water for 48 h, and hydrazide hyaluronic acid with a hydrazide degree of 20% was obtained after freeze-drying.
[0063] Then, hyaluronate-treated nano-aluminum nitride was prepared. The specific steps were as follows: 2 mg of HHA was dissolved in 1 mL of a dimethyl sulfoxide / water mixture with a volume ratio of 3:1; then, 2 mg of aluminum nitride with a particle size of 55 nm was ultrasonically dispersed in 1 mL of dimethyl sulfoxide, added dropwise to the hydrazide-treated hyaluronic acid solution, and stirred for 1 hour under magnetic stirring at 1400 rpm; then, the product was collected by centrifugation and washed with water 3 times to obtain hyaluronate-treated aluminum nitride nanoparticles.
[0064] Finally, self-adjuvanted nanomedicines containing copper peroxide quantum dots in the shell were prepared in situ by copper-hydrazide coordination / mineralization reaction. The specific steps are as follows: 2 mg of hyaluronate aluminum nitride nanoparticles were uniformly dispersed in 1 mL of water, and then slowly dropped into 1 mL of 1 mg / mL CuCl2 solution under vigorous stirring, wherein the mass ratio of hyaluronate aluminum nitride nanoparticles to copper chloride was 2:1. After stirring for 5 min, 200 μL of 2.5 mg / mL NaOH solution was slowly added, and then 12.5 μL of 30% H2O2 aqueous solution was added after 5 min. Finally, after reacting under magnetic stirring at 1500 rpm for 30 min, the precipitate was collected by centrifugation and washed with water 3 times to obtain self-adjuvanted nanomedicine loaded with copper peroxide.
[0065] Since aluminum adjuvants represented by aluminum hydroxide play an irreplaceable role in humoral immunity, they can promote the maturation of dendritic cells and greatly improve the efficiency of immune presentation. Therefore, the present invention will use nano aluminum nitride to load nano copper peroxide, which can not only generate nano aluminum hydroxide adjuvant in situ in tumor cells, but also react with acid in the tumor microenvironment to generate NH3 and then cause ammonia poisoning, thereby reversing the immunosuppressive microenvironment and efficiently activating tumor immunity. At the same time, the loaded nano copper peroxide has the ability to self-supply hydrogen peroxide and consume glutathione, which removes obstacles for CDT treatment. Therefore, the self-adjuvanted nano drug constructed by the present invention has acidic / glutathione dual response characteristics, and can efficiently kill tumor cells through chemical kinetic effects, reversal of immunosuppressive microenvironment, self-generated strong nano aluminum adjuvant to regulate tumor immunity, etc.
[0066] The above description is only for the best embodiment of the present invention, but it should not be understood as limiting the claims. The present invention is not limited to the above embodiments, and its specific structure is allowed to be changed. However, all changes made within the protection scope of the independent claims of the present invention are within the protection scope of the present invention.
[0067] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
Claims
1. A method for preparing a self-adjuvanted nano drug loaded with copper peroxide, characterized in that: The following steps are involved: preparing hydrazide hyaluronic acid; The hydrazide hyaluronic acid is modified on the surface of the nano-aluminum nitride through coordination and electrostatic adsorption to obtain the hyaluronic acid nano-aluminum nitride; Hyaluronan-coated nanoaluminum nitride was used to prepare copper peroxide-loaded self-adjuvanted nanodrugs in situ via copper-hydrazide coordination / mineralization reaction.
2. The method for preparing the self-adjuvanted nano drug loaded with copper peroxide according to claim 1, characterized in that: The specific synthesis steps of hydrazide hyaluronic acid are as follows: add 3,3'-dithiodipropionyl hydrazide and N-hydroxysuccinimide to the hyaluronic acid aqueous solution, adjust the pH to 5 to 5.5, then add 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, stir at 30 to 35°C for 12 to 48 hours, dialyze the reaction system against water for 8 to 48 hours, and freeze-dry to obtain hydrazide hyaluronic acid.
3. The method for preparing the self-adjuvanted nano drug loaded with copper peroxide according to claim 2, characterized in that: The concentration of the hyaluronic acid aqueous solution is 10 to 20 mg / mL, the mass ratio of hyaluronic acid: N-hydroxysuccinimide: 3,3'-dithiodipropionyl hydrazide: 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride is 10:1:12:1.5 to 10:3:36:4.5, the molecular weight of hyaluronic acid is 8 to 10 kDa, and the hydrazide degree of hydrazide hyaluronic acid is 20% to 60%.
4. The method for preparing the self-adjuvanted nano drug loaded with copper peroxide according to claim 1, characterized in that: The specific synthesis steps of hyaluronate-treated nano-aluminum nitride are as follows: uniformly mixing a suspension of aluminum nitride in dimethyl sulfoxide and a mixed solution of hydrazide-treated hyaluronic acid in dimethyl sulfoxide and water to obtain hyaluronate-treated aluminum nitride nanoparticles.
5. The method for preparing the self-adjuvanted nano drug loaded with copper peroxide according to claim 4, characterized in that: The mass ratio of hydrazide hyaluronic acid to aluminum nitride is 1 to 5:1; The volume ratio of dimethyl sulfoxide to water in the dimethyl sulfoxide / water mixture is 3:1 to 5:1; Homogenous mixing was achieved by stirring at 800 to 1500 rpm for 1 to 4 h.
6. The method for preparing the copper peroxide-loaded self-adjuvanted nano drug according to claim 1, characterized in that: The specific synthesis steps of the self-adjuvanted nanomedicine loaded with copper peroxide are as follows: a nanosuspension of hyaluronate aluminum nitride nanoparticles is mixed evenly with a copper chloride solution, a NaOH aqueous solution is added and mixed evenly, and then a H2O2 aqueous solution is added and mixed evenly to obtain a self-adjuvanted nanomedicine loaded with copper peroxide.
7. The method for preparing the self-adjuvanted nano drug loaded with copper peroxide according to claim 6, characterized in that: The concentration of the nanosuspension of hyaluronanized aluminum nitride nanoparticles is 1 to 5 mg / mL, the concentration of the copper chloride solution is 1 to 2 mg / mL, and the mass ratio of the hyaluronanized aluminum nitride nanoparticles to the copper chloride is 1:1 to 4:
1.
8. The method for preparing the self-adjuvanted nano drug loaded with copper peroxide according to claim 7, characterized in that: The concentration of the NaOH aqueous solution is 0.5 ~ 2.5 mg / mL, the mass fraction of the H2O2 aqueous solution is 10% ~ 30%, and the volume ratio of the hyaluronic acid aluminum nitride nanoparticle nanosuspension, the NaOH aqueous solution and the H2O2 aqueous solution is 1 ~ 5mL:10 ~ 100 μL:6.25~ 100 μL.
9. A self-adjuvanted nanomedicine loaded with copper peroxide prepared according to the method of any one of claims 1 to 8, characterized in that: The self-adjuvanted nano drug has a particle size of 100 to 300 nm, and has the performance of being able to consume glutathione, self-supply H2O2, self-generate nano aluminum adjuvant, and have Fenton-like catalytic activity.
10. Use of a self-adjuvanted nano drug loaded with copper peroxide prepared according to the method of any one of claims 1 to 8 in preparing a drug for treating malignant melanoma.